Effectiveness of a Technology‐Based Intervention to Teach Evidence‐Based Practice: The EBR Tool. Issue 1 (15th January 2016) - Long, JoAnn D.; Gannaway, Paula; Ford, Cindy; Doumit, Rita; Zeeni, Nadine; Sukkarieh‐Haraty, Ola; Milane, Aline; Byers, Beverly; Harrison, LaNell; Hatch, Daniel; Brown, Justin; Proper, Sharlan; et al.
ABSTRACT: Background: As the world becomes increasingly digital, advances in technology have changed how students access evidence‐based information. Research suggests that students overestimate their ability to locate quality online research and lack the skills needed to evaluate the scientific literature. Clinical nurses report relying on personal experience to answer clinical questions rather than searching evidence‐based sources. To address the problem, a web‐based, evidence‐based research (EBR) tool that is usable from a computer, smartphone, or iPad was developed and tested. The purpose of the EBR tool is to guide students through the basic steps needed to locate and critically appraise the online scientific literature while linking users to quality electronic resources to support evidence‐based practice (EBP). Methods: Testing of the tool took place in a mixed‐method, quasi‐experimental, and two‐population randomized controlled trial (RCT) design in a U.S. and Middle East university. Results: A statistically significant improvement in overall research skills was supported in the quasi‐experimental nursing student group and RCT nutrition student group using the EBR tool. A statistically significant proportional difference was supported in the RCT nutrition and PharmD intervention groups in participants' ability to distinguish the credibility of online source materials compared with controls. The majority of participants could correctly apply PICOTS to a case study when using the tool. Conclusions: The data from this preliminary study suggests that the EBR tool enhanced student overall research skills and selected EBP skills while generating data for assessment of learning outcomes. Linking Evidence to Action: The EBR tool places evidence‐based resources at the fingertips of users by addressing some of the most commonly cited barriers to research utilization while exposing users to information and online literacy standards of practice, meeting a growing need within nursing curricula.